تخفيض عامل (مودول) القص في آليات القص القرصية العاملة بالاحتكاك المستخدمة في قص قضبان الخطوط الحديدية - الاحمد نوفل; يوسف نزيه (Latakia University Journal -Engineering Sciences Series, 2019)
يتلخص البحث في إيجاد طريقة لقص القضبان الحديدية بحيث يتم فيها تخفيض عامل الاحتكاك أو ما يسمى عامل القص. إن عملية القص لقضبان الخطوط الحديدية تكتسب أهمية كبرى في حالة الخطوط الملحومة؛ إذ إن حدوث أعطاب و تشوهات في قضبان الخطوط تستوجب إزالتها حتى لا تكون السبب في الحوادث أو في تآكل دواليب القوام المتحرك في القطارات بالإضافة إلى حدوث اهتزازات تزعج الركاب في قطارات نقل الركاب . تشمل الدراسة الأسس النظرية والمعادلات الرياضية التي تربط بين درجات الحرارة وسرعة القرص وعامل التمدد الطولي لمعدن قضيب الخط الحديدي وزمن عملية القص بإدخال حركة اهتزازية إضافية وإجراء التجارب الميدانية تمت مقارنتها مع هذه الأسس وبالتالي الخروج بنتائج مفيدة. This paper aims to invent a new method for cutting rail-rods so that the friction will be reduced. The cutting process of rail-rods is very important especially in case of welded rails. So the occurrence of faultts and defects in railways must be removed to prevent accidents (train derailment) or fretting of model wheels and vibration causing inconvenience on passenger train. This study contains the basics of theoretical and mathematical equation that show the relationship between temperature and cutting speed. Also, it deals with linear expansion (also linear forces) and expansion module for the metal rod used on railways and the time of cutting process by using an additional vibrating movement in the cutting process. Many experiments have been carried out and the results obtained have been compared with the theoretical ones